Is the Osmolal Concentration of Ethanol Greater Than Its Molar Concentration? - Nguyen, Minhtri K.; Song, Lu; Kao, Liyo; Tong, Kevin; De La Cruz, Maria J.; Rodriguez, Giancarlo; Nguyen, Minh-Kevin; Nguyen, Dai-Scott; Kurtz, Ira (Frontiers in Medicine, 2020)
Background Recent data suggested that the osmolar gap attributed to ethanol as determined by the difference between measured serum osmolality and calculated serum osmolarity is greater than its molar concentration. The increased osmotic activity of ethanol is thought to be due to its binding to water molecules. This study is conducted to determine the true osmotic contribution of ethanol to serum osmolality. Methods Baseline serum osmolality and ethanol concentration were measured on each serum sample. Varying amounts of ethanol were added to aliquots of serum in which the baseline serum ethanol concentration was undetectable. Repeat serum osmolality and serum ethanol concentration were measured after addition of ethanol. Results The range of serum ethanol concentration was 27.3 to 429.8 mg/dL. The serum osmolar gap attributed solely to ethanol is calculated based on the difference between measured serum osmolality before and measured serum osmolality after addition of ethanol. Our results demonstrated that the contribution of ethanol to serum osmolality can be calculated by dividing the serum ethanol level in mg/dl by 4.6. In addition, the relationship between serum ethanol concentration and osmolar gap due to ethanol was assessed by linear regression analysis. Linear regression analysis relating the osmolar gap due to ethanol and ethanol concentration yielded the following equation: Osmolar Gap (mOsm/kg H2O) = 0.23 (Ethanol [mg/dL]) – 1.43. Conclusion The osmolar concentration of ethanol can be calculated based on its molar concentration. We found no evidence for ethanol binding to water molecules over the range of ethanol concentration in this study.